Novel Herbal Medicine C-KOK Suppresses the Inflammatory Gene iNOS via the Inhibition of p-STAT-1 and NF-κB - Lee, In-Chul; Ryu, Chang-Woo; Bae, Jong-Sup (Biotechnology and bioprocess engineering, 2020)
Cheong-Pye-Ko (CPK) and Kyung-Ok-Ko (KOK) are traditional herbal medicine prescriptions that have been used in oriental medicine as tonics for pulmonary-related diseases for centuries. However, the effects of a mixture of CPK and KOK (C-KOK) on cytokine-mediated pulmonary damage have not yet been elucidated. This study used lipopolysaccharide (LPS)-activated human pulmonary artery endothelial cells (HPAECs) to examine the effects of C-KOK on the induction of heme oxygenase-1 (HO-1) and the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). Moreover, a mouse model was used to determine if C-KOK affected the expression of tumor necrosis factor (TNF)-α and iNOS in the lung tissues of LPS-treated mice. The results showed that C-KOK induced the translocation of Nrf2 from the cytosol to the nucleus by increasing Nrf2-antioxidant response elements (ARE) activity, increased the expression of HO-1, and decreased IL-1β and iNOS/NO production in the LPS-activated HPAECs. Specifically, the suppression of iNOS/NO expression from the administration of C-KOK was reversed by the RNAi knockdown of HO-1. In conclusion, these findings indicated that C-KOK produced a critical anti-inflammatory effect due to its HO-1 dependent downregulation of p-STAT-1 and NF-κB and the resultant inhibition of iNOS and also suggested that TNF-α was a potential target for HO-1. Therefore, the administration of C-KOK showed efficacy and might be a novel approach for the treatment of inflammatory pulmonary disease.